Achievement of high coercivity in Sm(Fe0.8Co0.2)12 anisotropic magnetic thin film by boron doping. (1st August 2020) - Sepehri-Amin, H.; Tamazawa, Y.; Kambayashi, M.; Saito, G.; Takahashi, Y.K.; Ogawa, D.; Ohkubo, T.; Hirosawa, S.; Doi, M.; Shima, T.; Hono, K.
Abstract: SmFe12 -based compounds have been considered as promising candidates for next generation permanent magnet materials because of their excellent intrinsic hard magnetic properties with a minimum usage of rare earth elements. However, realizing high coercivity in anisotropic microstructure is a big challenge, which hinders their practical applications. In this work, a novel anisotropic granular microstructure of Sm(Fe0.8 Co0.2 )12 with a sufficiently large coercivity ( µ 0 H c ) of 1.2 T and with a high remanent magnetization of 1.50 T is demonstrated in thin films prepared by co-sputtering Sm(Fe, Co)12 with boron. Detailed microstructure characterization using high resolution scanning transmission electron microscopy (STEM) and atom probe tomography (APT) indicate that the addition of B leads to the development of columnar-shaped Sm(Fe0.8 Co0.2 )12 grains with a size of ∼40 nm, which are surrounded by ∼3 nm-thick B-enriched amorphous intergranular phase. Domain wall pinning at the amorphous grain boundary phase is attributed to the high coercivity. This work provides a guiding principle for realizing high-coercivity anisotropic SmFe12 -based permanent magnets, which can outperform Nd-Fe-B magnets and could be used as the next-generation high-performance permanent magnets in various applications. Graphical abstract: Image, graphical abstract